Effect of different rooting media on stem cuttings of Eucalyptus pellita F. Muell - Julius Kodoh; Y.L. Chen; M. Maid; H. Affendy (Sabah Forestry Department, 2018)
The use of woody stem cuttings as propagation material is vital when seeds are insufficient and when producing clonal material. The objectives of this study were to determine the survival rate and rooting ability of Eucalyptus pellita stem cuttings from different portions of the stem and using different rooting media. Three portions of stem cutting (apical, median and basal) at 5 to 10 cm length were obtained from three-month-old E. pellita seedlings. Each stem cutting contained two trimmed apex leaves, and then rooting hormone (IBA) was applied as a root booster. Three rooting media were used, namely river sand, black soil and coco peat. The experiments consisted of 3 treatments and 3 replications. Data were collected bi-weekly for 14 weeks. The assessment for rooting ability was performed after four weeks of planting. The result obtained showed river sand is the best rooting media and apical part as the most suitable part to be propagated.